The distribution and abundance of archaeal tetraether lipids in U.S. Great Basin hot springs - Paraiso, Julienne J.; Williams, Amanda J.; Huang, Qiuyuan; Wei, Yuli; Dijkstra, Paul; Hungate, Bruce A.; Dong, Hailiang; Hedlund, Brian P.; Zhang, Chuanlun (Frontiers in Microbiology, 2013)
Isoprenoidal glycerol dialkyl glycerol tetraethers (iGDGTs) are core membrane lipids of many archaea that enhance the integrity of cytoplasmic membranes in extreme environments. We examined the iGDGT profiles and corresponding aqueous geochemistry in 40 hot spring sediment and microbial mat samples from the U.S. Great Basin with temperatures ranging from 31 to 95°C and pH ranging from 6.8 to 10.7. The absolute abundance of iGDGTs correlated negatively with pH and positively with temperature. High lipid concentrations, distinct lipid profiles, and a strong relationship between polar and core lipids in hot spring samples suggested in situ production of most iGDGTs rather than contamination from local soils. Two-way cluster analysis and non-metric multidimensional scaling (NMS) of polar iGDGTs indicated that the relative abundance of individual lipids was most strongly related to temperature (r2 = 0.546), with moderate correlations with pH (r2 = 0.359), nitrite (r2 = 0.286), oxygen (r2 = 0.259), and nitrate (r2 = 0.215). Relative abundance profiles of individual polar iGDGTs indicated potential temperature optima for iGDGT-0 (≤70°C), iGDGT-3 (≥55°C), and iGDGT -4 (≥60°C). These relationships likely reflect both physiological adaptations and community-level population shifts in response to temperature differences, such as a shift from cooler samples with more abundant methanogens to higher-temperature samples with more abundant Crenarchaeota. Crenarchaeol was widely distributed across the temperature gradient, which is consistent with other reports of abundant crenarchaeol in Great Basin hot springs and suggests a wide distribution for thermophilic ammonia-oxidizing archaea (AOA).